IMPLEMENTASI ALGORITMA ANALYTICAL HIERARCHY PROCESS (AHP) DALAM APLIKASI PENJUALAN ONLINE DENGAN STUDI KASUS : LAUREN’S CLOTHES - Juvrience Marcius Lim; Roelly Hoemdiana (Jurnal Informatika dan Bisnis, 2021)
Lauren's Clothes is currently experiencing difficulties because with the sales media used, the profits obtained are not optimal because in the marketplace there are administrative costs, there is limited space in building a brand image in accordance with the wishes of the business owner. Prospective buyers also often have difficulty in determining the product to be purchased due to the many attractive choices. This study aims to implement the Analytical Hierarchy Process (AHP) algorithm in the sales application of Lauren's Clothes to support customer decisions in determining the appropriate product. This study uses the Personal eXtreme Programming (PXP) method where the method is designed for one developer. The research data were collected through interviews, observation and literature study. The result of this research is a sales application of Lauren's Clothes which has the Analytical Hierarchy Process (AHP) feature for customers in determining the product they want to buy.   Keywords: Analytical Hierarchy Process, AHP, Sales Application, E-commerce.